1992
DOI: 10.1002/bjs.1800790934
|View full text |Cite
|
Sign up to set email alerts
|

Fat-wrapping in Crohn's disease: Pathological basis and relevance to surgical practice

Abstract: The connective tissue changes that accompany intestinal Crohn's disease have received little attention from pathologists. This is particularly so with fat hypertrophy, and yet surgeons have long recognized the phenomenon of fat-wrapping in the intestines and used it to delineate the extent of active disease. A consecutive, unselected series of 27 intestinal resections performed on 25 patients for histologically confirmed Crohn's disease was studied to correlate fat-wrapping with other clinicopathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 11 publications
5
165
0
2
Order By: Relevance
“…These Crohn's disease lesions involve the intestinal serosa and mesentery. The characteristic changes in the serosal surface, including fat wrapping, correlate directly with overall extent of inflammatory changes: the stricture of the intestine (10,11), the depth of lymphoid aggregate penetration, and the number of lymphoid aggregates in the underlying ileal wall (12). These observations suggest that inflammation of viscera is not limited to the organ, but provokes responses in the peritoneal cavity as well.…”
Section: Inhibition Of Ccl1-ccr8 Interaction Prevents Aggregation Of mentioning
confidence: 93%
“…These Crohn's disease lesions involve the intestinal serosa and mesentery. The characteristic changes in the serosal surface, including fat wrapping, correlate directly with overall extent of inflammatory changes: the stricture of the intestine (10,11), the depth of lymphoid aggregate penetration, and the number of lymphoid aggregates in the underlying ileal wall (12). These observations suggest that inflammation of viscera is not limited to the organ, but provokes responses in the peritoneal cavity as well.…”
Section: Inhibition Of Ccl1-ccr8 Interaction Prevents Aggregation Of mentioning
confidence: 93%
“…• The findings of increased adipose tissue in intestinal segments in patients with Crohn's disease, known as "fat wrapping," have clearly shown that inflammation plays an important role [17,[26][27].…”
Section: Excess Subcutaneous Adiposity and Chronic Lymphedemamentioning
confidence: 99%
“…Although this anomalous hypertrophy of adipose tissue appears to be a primary defect in Crohn's disease (Sheehan et al 1992;Desreumaux et al 1999), it has not featured prominently in the extensive, and in many cases sophisticated, research into its pathology. Of more than 6000 papers about Crohn's disease published during the last 20 years, only eleven (less than 0·2 %) mention adipose tissue.…”
Section: Crohn's Diseasementioning
confidence: 99%